A two-step risk assessment method for radiofrequency ablations of spine metastases. (May 2019) - Merten, N.; Adler, S.; Hille, G.; Hanses, M.; Becker, M.; Saalfeld, S.; Preim, B.
Abstract: Background: Spine metastases (MTS) can be treated via Radiofrequency Ablation (RFA) electrodes. To bring these electrodes into vertebral MTS, pathways have to be created. This can be done via transpedicular hammering or drilling. However, this is challenging due to spatial constraints, and because MTS can alter bone density considerably. Method: In this work a two-step method is presented that intends to offer cognitive and physical assistance. Step 1 comprises two visualization methods that depict safety margins between and in risk structures. For Step 2, the correlation between Hounsfield Units (HUs) and drilling forces was analyzed to support manual and robot-assisted RFAs. Results: In-depth descriptions of two clinical cases and detailed feedback from the local clinic of neuroradiology are used to present the capabilities of the proposed method. Furthermore, a stiffness criterion is presented to predict drilling force changes from the local distribution and homogeneity of HUs with an inaccuracy of less than 1 mm. Conclusions: The combination of visualization and drilling force prediction shows potential to support manual and robot-assisted spine RFAs. However, limitations have to be addressed in the future. For example, it has to be carefully evaluated to which extent the proposed method can speed up the planning process and increase intervention safety. Graphical abstract: Image 1